Phenomic Analysis of Chronic Granulomatous Disease Reveals More Severe Integumentary Infections in X-Linked Compared With Autosomal Recessive Chronic Granulomatous Disease - Chiu, Timothy Lok-Hin; Leung, Daniel; Chan, Koon-Wing; Yeung, Hok Man; Wong, Chung-Yin; Mao, Huawei; He, Jianxin; Vignesh, Pandiarajan; Liang, Weiling; Liew, Woei Kang; Jiang, Li-Ping; Chen, Tong-Xin; et al. (Frontiers in Immunology, 2022)
Background Chronic Granulomatous Disease (CGD) is an inborn error of immunity (IEI), characterised by recurrent bacterial and fungal infections. It is inherited either in an X-linked (XL) or autosomal recessive (AR) mode. Phenome refers to the entire set of phenotypes expressed, and its study allows us to generate new knowledge of disease. The objective of the study is to reveal the phenomic differences between XL and AR-CGD by using Human Phenotype Ontology (HPO) terms. Methods We collected data on 117 patients with genetically diagnosed CGD from Asia and Africa referred to the Asian Primary Immunodeficiency Network (APID network). Only 90 patients with sufficient clinical information were included for phenomic analysis. We used HPO terms to describe all phenotypes manifested in the patients. Results XL-CGD patients had a lower age of onset, referral, clinical diagnosis and genetic diagnosis compared with AR-CGD patients. The integument and central nervous system were more frequently affected in XL-CGD patients. Regarding HPO terms, perianal abscess, cutaneous abscess and elevated hepatic transaminase were correlated with XL-CGD. A higher percentage of XL-CGD patients presented with BCGitis/BCGosis as their first manifestation. Among our CGD patients, lung was the most frequently infected organ, with gastrointestinal system and skin ranking second and third respectively. Aspergillus species, Mycobacterium bovis and Mycobacteirum tuberculosis were the most frequent pathogens to be found. Conclusion Phenomic analysis confirmed that XL-CGD patients have more recurrent and aggressive infections compared with AR-CGD patients. Various phenotypic differences listed out can be used as clinical handles to distinguish XL or AR-CGD based on clinical features.